Psychology and the Paranormal by David F. Marks - Kennedy, James E (Journal of Scientific Exploration, 2022)
David Marks’ previous book about the paranormal (Marks, 2000) and other earlier writings established his reputation as a firm skeptic. He wrote the current book in order to learn about new developments in paranormal research during the past 20 years. The overall conclusion in this book is that Marks now believes that spontaneous paranormal phenomena may occur, but psi is a spontaneous process that cannot be controlled and demonstrated in laboratory experiments. His belief that instances of spontaneous psi may occur is based largely on a personal experience of synchronicity that had layers of meaning for him. The experience is described and evaluated in chapter four. He rates the probability as 75% that the experience had a paranormal component.